IMPLEMENTASI SISTEM RUJUKAN TERINTEGRASI (SISRUTE) INSTALASI GAWAT DARURAT DI RSUD TOTO KABILA - Trilaila Kadir; Riska Ahmad; Moh Ichsan Arifin Antu (MOTORIK Jurnal Ilmu Kesehatan, 2025)
The Integrated Referral System (SISRUTE) is a technological innovation in health services designed to accelerate, simplify, and clarify the patient referral process between healthcare facilities electronically. This system plays a crucial role, especially in emergency services that demand rapid and accurate coordination. However, its implementation at RSUD Toto Kabila remains suboptimal. Key issues include the absence of written Standard Operating Procedures (SOP), limited technical training for health personnel, and unstable internet connectivity. This study aims to describe the implementation of SISRUTE at the Emergency Department of RSUD Toto Kabila Bone Bolango and identify obstacles encountered during the process. This is a qualitative study using a phenomenological approach and source triangulation technique. The research was conducted from May to June 2025 involving five informants from medical and administrative personnel. The findings reveal that SISRUTE implementation is still partial and heavily reliant on admission staff, with minimal involvement from doctors and nurses. The application tends to be slow in emergency situations, and the referral flow is not yet standardized. The study concludes that managerial improvements, cross-professional training, and reinforcement of a technology-oriented work culture are essential to ensure effective and sustainable implementation of SISRUTE.